LincRNA-MSTRG.673.2 Promotes Chicken Intramuscular Adipocyte Differentiation by Sponging miR-128-3p - Binbin Zhang; Shuaipeng Zhu; Yuehua He; Wenjie Liang; Tingqi Zhu; Ruili Han; Donghua Li; Yanbin Wang; Yadong Tian; Guoxi Li; Xiangtao Kang; Wenting Li; et al. (Animals)
Background: Intramuscular fat content is positively correlated with meat flavor and juiciness. Increasing the intramuscular fat (IMF) content of chickens while increasing their growth rate has become a hot topic in molecular breeding. The group’s previous studies showed that miR-128-3p inhibited chicken intramuscular adipocyte differentiation and lipogenesis. However, the regulatory mechanism of miR-128-3p in intramuscular preadipocytes is currently unknown. In this study, we investigated the mechanism of miR-128-3p regulation of chicken intramuscular adipocyte differentiation and deposition. Results: Transcriptome data analysis of differential LincRNAs indicated that, compared to the NC group, the mimics-treated group had seventeen significantly differentially expressed LincRNAs (p < 0.05), including six upregulated and eleven downregulated ones; the inhibitor-treated group had seventeen differentially expressed LincRNAs (p < 0.05), including eight upregulated and nine downregulated ones; and twenty-four differentially expressed LincRNAs (p < 0.05) were observed when comparing the mimics-treated group to the inhibitor-treated group, with fourteen upregulated and ten downregulated ones. Functional enrichment analysis revealed that DELincRNAs from the overexpression group (M group) and interference group (SI group) were involved in the negative regulation of metabolic processes, response to steroid hormones, and regulation of actin cytoskeleton. Furthermore, target gene prediction analysis showed that miR-128-3p can target many of the DELincRNAs, such as LincRNA-MSTRG.673.2, LincRNA-MSTRG.39.2, LincRNA-MSTRG.39.3, and LincRNA-MSTRG.14270.2. LincRNA-MSTRG.673.2 was predominantly expressed in the cytoplasm of intramuscular adipocytes. Dual luciferase reporter identified the targeting relationship between miR-128-3p and LincRNA-MSTRG.673.2. The results of subsequent functional assays demonstrated that interfering with MSTRG.673.2 has been shown to inhibit lipid deposition in intramuscular preadipocytes. Transfection experiments have shown that LincRNA-MSTRG.673.2 can affect the expression of miR-128-3p. Conclusions: This study found that LincRNA-MSTRG.673.2 promoted chicken intramuscular adipocyte differentiation by downregulating miR-128-3p. The results are noteworthy for improving chicken meat quality, molecular breeding, and lipid metabolism research.